Clinical presentation and management of nephrotic syndrome in the first year of life: A report from the Pediatric Nephrology Research Consortium - Constantinescu, Alexandru R.; Mattoo, Tej K.; Smoyer, William E.; Greenbaum, Larry A.; Niu, Jianli; Howard, Noel; Muff-Luett, Melissa; Benoit, Elizabeth B.; Traum, Avram; Annaim, Ali A.; Wenderfer, Scott E.; Plautz, Emilee; et al. (Frontiers in Pediatrics, 2022)
ABSTRACT Background and objectives: Nephrotic syndrome (NS) in the first year of life is called congenital (CNS) if diagnosed between 0-3 months, or infantile (INS) if diagnosed between 3-12 months of age. The aim of this study was to determine if there were clinically meaningful differences between CNS and INS patients, regarding clinical presentation, management and outcomes. Design, setting, participants and measurements: Eleven Pediatric Nephrology Research Consortium sites participated in the study, using IRB-approved retrospective chart reviews of CNS and INS patients born between 1998 and 2019. Data were collected on patient characteristics, pertinent laboratory tests, provided therapy, timing of unilateral/bilateral nephrectomy and initiation of renal replacement therapy (RRT). Results: The study included 69 patients, 49 with CNS and 20 with INS, with a median age at diagnosis of one and six months, respectively. Management for the two groups was similar regarding nutrition, thyroxin supplementation, immunoglobulin administration, and thrombosis prophylaxis. Within the first 2 months after diagnosis, daily albumin infusions were used more often in CNS vs. INS patients (79 vs. 30%; p=0.006), while weekly infusions were more common in INS patients (INS vs. CNS: 50 vs. 3%; p=0.001). During the six months preceding RRT, albumin infusions were more frequently prescribed in CNS vs. INS (51% vs. 15%; p=0.007). Nephrectomy was performed more often in CNS (78%) than in INS (50%; p=0.02). End-stage kidney disease tended to be more common in children with CNS (80%) vs. INS (60%; p=0.09). Conclusions: Compared to INS, patients with CNS had a more severe disease course, requiring more frequent albumin infusions, and earlier nephrectomy and RRT. Despite center-specific variations in patient care, 20-40% of patients did not require nephrectomy or RRT.